If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 58x = 57x + 1 Reorder the terms: -1 + 58x = 1 + 57x Solving -1 + 58x = 1 + 57x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-57x' to each side of the equation. -1 + 58x + -57x = 1 + 57x + -57x Combine like terms: 58x + -57x = 1x -1 + 1x = 1 + 57x + -57x Combine like terms: 57x + -57x = 0 -1 + 1x = 1 + 0 -1 + 1x = 1 Add '1' to each side of the equation. -1 + 1 + 1x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + 1x = 1 + 1 1x = 1 + 1 Combine like terms: 1 + 1 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| 3G-2g=12 | | 5-3=15 | | -y=5x+4 | | -8q=6 | | 4.9t^2-13t-64=0 | | -21(x+y)= | | 17m-15m=6 | | 3(0)-2=y | | 7x-3-127=180 | | y=-4/3(-1.333)-8 | | 3x+19+4x+-2=180 | | -4y=3x-12 | | 2=-2(u+4) | | -3(m+2)-4=-12-(-2+m) | | 5-4x-1+(x)=-23 | | 8x+3=109 | | 2x-10+x=38 | | 2b-b=19 | | 3x+19+4x+-4=180 | | 6(9v-3)=22 | | -1-4(-1)+y=15 | | -15+2x=37 | | 200/12=42/q | | 2=9v-3 | | 4z-4=-28+2 | | 5h-7=5(h-2)+3BC | | y+a=24 | | 2x^3+7x^2-3x+6=0 | | x+56+131=180 | | 9(-4t)=432 | | 3(3x+4)+4x=-92 | | 6x^2+42x+6y^2-15=0 |